Использование подхода предметно-языкового интегрированного обучения (CLIL) на уроках математики - Жабыкбаева, А.Х.; Сулейменова, Н.Ж. (My University, 2016)
The article is devoted to the principles and key concepts of Content and language integrated learning (CLIL). It presents a variety of activities aimed at the study of the subject through language and language learning through the content of the subject. It shows benefits of this technique. The article is written for a wide range of Mathematics teachers using this approach.
Keywords: integration; higher-order thinking skills; new approaches to teaching and learning; innovation